2005
DOI: 10.1021/la0502490
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Silver Films for Detection of Antibody−Antigen Binding

Abstract: Antibody-antigen binding events at a monolayer protein concentration have been demonstrated on nanostructured adaptive silver films (ASFs) using surface-enhanced Raman scattering (SERS) and luminescence-based assays. It is shown that proteins stabilize and restructure the ASF to increase the SERS signal while preserving antigen-binding activity. Evidence for antibody-antigen binding on the ASF substrates is the distinct SERS spectral changes of the surface-bound antibody or antigen without special tags. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 41 publications
1
51
0
Order By: Relevance
“…To date, a wide variety of strategies, such as vacuum deposition [9], oriented-assembly [10], nanoimprint lithography [11,12], colloidal lithography [13], nanosphere lithography [14], electron-beam lithography [15], have been employed to fabricate SERS-active substrates with sufficient Raman hot spots to achieve target molecules detection. Although the SERS substrates fabricated by these approaches have exhibited high sensitivity and reliability, the fabricating large-area SERS substrates through these approaches are usually expensive and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a wide variety of strategies, such as vacuum deposition [9], oriented-assembly [10], nanoimprint lithography [11,12], colloidal lithography [13], nanosphere lithography [14], electron-beam lithography [15], have been employed to fabricate SERS-active substrates with sufficient Raman hot spots to achieve target molecules detection. Although the SERS substrates fabricated by these approaches have exhibited high sensitivity and reliability, the fabricating large-area SERS substrates through these approaches are usually expensive and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…The observed signals were attributed mainly to the antigen-aptamer complex that positioned the antigen closer to the plasmonic near-fields on the SERS-active Au surface. In another example, Drachev et al reported on the detection of antigen-antibody binding events using adaptive Ag island films [112]. According to Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their resonant response and fractal morphology, random metal-dielectric composite systems can localize electromagnetic energy in nanometer-sized regions called hot spots, and they can also produce large near-field enhancement of electric and magnetic fields in the visible and infrared spectral ranges. [9][10][11][12] Materials placed in the near-field region of a random MDC film experience dramatically enhanced optical responses; this feature is employed in applications such as highly sensitive surface-enhanced Raman spectroscopies [13][14][15][16][17] and surface-enhanced infrared absorption spectroscopies, [18][19][20][21] enhanced solar cell efficiencies, 22,23 or for developing novel optical elements such as optical filters with transparency windows that can be controlled by local photomodification in the composites. 24,25 Due to their varying applications, MDCs have been a topic of research for many decades.…”
Section: Introductionmentioning
confidence: 99%